Analysis the effect of different type valve use at different pressure in piping system - Muzakkir, Shukri (2010)
This project was carried out as a study of flow rate using a single channel acoustic emission (AE) technique. The objective of this project is to study the effect of ball valve, brass gate valve and brass stop cock valve to flow rate using AE technique. A test rig consists of the circumferential galvanized steel pipe, ball valve, gate valve and stop cock valve to run the experiments. The fluid used was water throughout the experiments. The pressure of water was controlled by a valve. The source of AE signal was from the valve and it was captured using AE sensor with the help of Acoustic Emission Detector 2.1.3 software. For all valve conditions, the value of hits, count and RMS (average, maximum and minimum) were recorded and analyzed. All the value recorded were compared among the ball valve, gate valve and stop cock valve. The results were gained from 10 marked points each for all type of valve. The result showed that there was no AE activity on the pipe without valve, the AE activities are greater for high pressure or full close valve. In addition from the RMS against distance graft, RMS value increased when pressure is increased. From the flow rate against RMS graf show that flow rate will decrease when RMS is increased.